Pharmacovigilance: Urgent need in midwestern region of Nepal - Khanal, S; Gyawali, S; Kanodia, R; Rathor, RS (Kathmandu University Medical Journal, 2010)
DOI: 10.3126/kumj.v7i4.2776 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 470